Assessment of Risk Factors, Clinical Presentations and Predictors of Stroke Admitted in a Tertiary Care Center of Madhesh Province (Med Phoenix, 2025)
Introduction: Stroke is the second-leading global cause of death behind heart disease and is a major cause of permanent disability. The risk factors for this condition are grouped as modifiable and non-modifiable factors. The study is designed with aim to assess risk factors, clinical presentations and predictors of stroke subtypes among adult patients visited the stroke unit.Materials and Methods: A hospital based cross sectional study conducted in National Medical College Teaching Hospital, Birgunj was conducted for 10 months (March 2023 to December 2023). A total of 100 subjects were enrolled after an ethical clearance taken from Institutional Review Committee and a proper consent taken from the concerned. Data was collected and entered in Microsoft Excel and analyzed using Statistical Package of Social Sciences (SPSS) version 20.Results: A total of 100 subjects of diagnosed stroke enrolled in this study had a mean age of 50.52± 7.0 years. The major participants were male comprising of 66 % (n=66). As per the World Health Organization (WHO) criteria for diagnosis of stroke, 56% (n=56) of the participants had ischaemic stroke while 44% were diagnosed with the hemorrhagic stroke. Hypertension (94%, n=90) was the most common risk factor, followed by family history (n=35), alcohol use (n=25), smoking habit (n=24) and heart failure (n=17). The most common clinical presentation was headache (85%), aphasia (62%), and hemiparesis (55%) as per the complaints and findings of the participants.Conclusion:The clinical features, risk factors and predictors of stroke in our study are similar to other low and middle resource countries. The findings of the study relates with the basic associations of the different factors with stroke and can be helpful predicting the diagnosis of stroke, enhancing the health education focused on reducing the stroke and launching large scale public health campaign for educating and raising awareness regarding the risk factors and its intervention.